Gambaran Pengetahuan Pasien Diabetes Melitus Tipe II Mengenai Manajemen Diabetes Melitus Pada Pesisir Pantai Kota Pekalongan - Arief Sulistyanto, Benny; Ramadani, Nur Indah; Azzahra, Aziza (PENA NURSING, 2025)
Diabetes mellitus is a metabolic disorder characterized by elevated blood glucose levels (hyperglycemia) resulting from abnormalities in insulin secretion, insulin action, or both. Knowledge about diabetes mellitus is crucial, as it significantly influences patients' ability to manage their condition. There are seven key pillars of diabetes management: maintaining a healthy diet, engaging in regular physical activity, taking prescribed medications, monitoring blood glucose levels, problem-solving, adopting healthy coping mechanisms, and reducing health risks. This study aimed to describe the level of knowledge among patients with type 2 diabetes mellitus regarding diabetes management. A quantitative descriptive research design was used, with total sampling as the sampling technique. Data were collected using a questionnaire. The results showed that among 76 respondents, 33 (43.4%) had good knowledge, 24 (31.6%) had moderate knowledge, and 19 (25.0%) had poor knowledge about diabetes management. These findings indicate that the majority of respondents have a good understanding of diabetes management. This study may serve as a reference for efforts to improve patient knowledge and support better diabetes self-management.